Simultaneous, endogenous, and bi-directional relationship between output, labour productivity, and employment: a 3SLS estimation of the employment version of Okun equation - Butkus, Mindaugas; Dargenytė-Kacilevičienė, Laura; Matuzevičiūtė, Kristina; Ruplienė, Dovilė; Šeputienė, Janina (Journal of Business Economics and Management, 2024)
Over the last few decades, the European Union (EU) has made progress in reducing economic disparities between Member States. However, persistent differences in employment rates remain, prompting a concerted effort to foster economic development conducive to job creation. However, the previous research does not address the impact of labour productivity on the output-employment relationship. While they provide insights into the complex interplay between productivity, output, and employment, they do not comprehensively analyse how labour productivity affects the output-employment relationship. Using panel data from 27 EU countries and the UK over 2000–2022, we aim to evaluate whether economic growth led by increased productivity can enlarge employment when the complexity of interrelationships is specified in the model. While initial estimates using pooled OLS and 2SLS methods yield insignificant results, 3SLS estimates reveal a significant mediating effect of productivity on the output-employment nexus. The results imply that raising labour productivity can boost employment prospects during economic expansions. However, the mediating effect weakens during downturns, highlighting the need for multifaceted policy interventions. These findings provide crucial insights for policymakers navigating the complex and challenging dynamics of employment and economic growth in the EU context.